Chitosan as therapeutical excipient in cancer nanomedicine development / Wong Tin Wui - Wui, Wong Tin (Faculty of Pharmacy, 2024)
The United States Food and Drug Administration defines nanomaterial or nanoproduct being characterized by at least one external dimension or an internal or surface structure, in the range of about 1 nm to 100 nm, or exhibit properties or phenomena, that are attributable to a dimension up to 1000 nm. Nanoparticles have been adapted to encapsulate, stabilize, and targeted delivery of various cancer chemotherapeutics. They can be formulated to provide passive as well as active targeting elements with the aim to improve drug efficacy and minimize adverse off-target reactions. The ultimate application of nanoparticles is to raise the drug bioavailability at tumour sites against the non-cancerous regions. In recent years, erythrocytes, platelets and exosomes have been proposed as the drug targeting devices. Nevertheless, nanoparticulate system remains as the system of choice since erythrocytes, platelets and exosomes are met with neoplastic risks and production hiccups.